1999
DOI: 10.1046/j.1365-2133.1999.03209.x
|View full text |Cite
|
Sign up to set email alerts
|

Late development of antidesmoglein 1 antibodies in pemphigus vulgaris: correlation with disease progression

Abstract: The coexistence of antidesmoglein 3 (Dsg3) and antidesmoglein 1 (Dsg1) autoantibodies is well described in patients with pemphigus vulgaris (PV); however, there is little evidence of sequential development of these two autoantibodies. Autoantibody responses to Dsg3 and Dsg1 were studied in seven PV patients over time by enzyme-linked immunosorbent assay, using baculovirus expressed recombinant fusion proteins. All patients had anti-Dsg3 IgG antibodies at presentation. Two patients developed anti-Dsg1 later in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 20 publications
2
31
0
5
Order By: Relevance
“…ELISA studies have shown that all PF sera contain autoantibodies against Dsg1, and sera from patients with mucosal-dominant PV react mainly against Dsg3 (2)(3)(4). PV patients who progress from mucosal to mucocutaneous lesions develop anti-Dsg1 in addition to anti-Dsg3 antibodies (5). The anti-Dsg antibodies in pemphigus sera are pathogenic, since neonatal mouse passive transfer studies have shown that the extracellular domains of Dsg1 and Dsg3 can adsorb out pathogenic antibodies from PF and PV sera, respectively, and affinity-purified anti-Dsg1 or anti-Dsg3 antibodies cause characteristic disease (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…ELISA studies have shown that all PF sera contain autoantibodies against Dsg1, and sera from patients with mucosal-dominant PV react mainly against Dsg3 (2)(3)(4). PV patients who progress from mucosal to mucocutaneous lesions develop anti-Dsg1 in addition to anti-Dsg3 antibodies (5). The anti-Dsg antibodies in pemphigus sera are pathogenic, since neonatal mouse passive transfer studies have shown that the extracellular domains of Dsg1 and Dsg3 can adsorb out pathogenic antibodies from PF and PV sera, respectively, and affinity-purified anti-Dsg1 or anti-Dsg3 antibodies cause characteristic disease (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24] Os pacientes produzem auto-anticorpos da subclasse IgG4, patogênicos, dirigidos contra a Dsg3 (forma mucosa) ou contra as Dsg1 e 3 (formas cutâneo-mucosas). 6,23,24 As lesões confinadas às mucosas podem, gradualmente, progredir com acometimento cutâneo. Em pacientes com lesões muco-cutâneas são detectados auto-anticorpos patogênicos que reconhecem um segundo e diferente epí-topo na Dsg3 e apresentam reação cruzada com a Dsg1.…”
Section: Epitope Spreading Intramolecular (Intraproteína) Pênfigo Vulgarunclassified
“…23 Portanto, o epitope spreading ocorre em pacientes cuja doença progride da forma mucosa para a cutâneo-mucosa, considerando a heterogeneidade da resposta dos anticorpos nesses pacientes. 6,24 Pênfigo foliáceo endêmico ou fogo selvagem Dermatose bolhosa auto-imune endêmica no Brasil e em outros países da América do Sul, que é mediada por auto-anticorpos patogênicos IgG4 contra a Dsg1. 25 Do ponto de vista clínico e imunológico, o PFE assemelha-se à forma clássica do PF.…”
Section: Epitope Spreading Intramolecular (Intraproteína) Pênfigo Vulgarunclassified
“…12 O psoraleno oral sob a radiação UVA foi avaliado no tratamento das erupções disidrosiformes e, quando comparado com o UVB, obteve melhor resultado. 24 O UVA sem psoraleno também foi benéfico. O UVA isoladamente obteve resultados similares aos do Puva tópico, que se mostraram superiores aos encontrados com UVB.…”
Section: Tratamentounclassified